Analisis Dampak Suku Bunga SBI, Inflasi, serta Pertumbuhan Ekonomi terhadap Return Saham Syariah Pada Jakarta Islamic Index Indonesia - Multazam, Agung (Iqtishodia: Jurnal Ekonomi Syariah, 2018)
This research is intended to determine the effect of SBI Interest Rate, Inflation, and Economic Growth on Sharia Stock Returns in JII (Jakarta Islamic Index) Period 2010-2017. This study uses a quantitative approach with the object of research on the company at the JII (Jakarta Islamic Index) registered in the period 2010-2017. With a total of 10 companies. The data collection technique uses purposive sampling. The data analysis technique used in answering the hypothesis of this study is multiple linear analysis. The results of this study indicate that partially the SBI Interest Rate has a significant positive effect on Sharia Stock Returns in the Jakarta Islamic Index, and Inflation has a significant negative effect and whereas Economic Growth has no influence on the Return of Sharia Stocks in JII. Simultaneous inflation research, SBI interest rates and economic growth have a significant effect on the return of Islamic stocks at JII.